Comparison of multi-coil and multi-frequency frequency domain electromagnetic induction instruments - Blanchy, Guillaume; McLachlan, Paul; Mary, Benjamin; Censini, Matteo; Boaga, Jacopo; Cassiani, Giorgio (Frontiers in Soil Science, 2024)
Introduction: Characterization of the shallow subsurface in mountain catchments is important for understanding hydrological processes and soil formation. The depth to the soil/bedrock interface (e.g., the upper ~5 m) is of particular interest. Frequency domain electromagnetic induction (FDEM) methods are well suited for high productivity characterization for this target as they have short acquisition times and do not require direct coupling with the ground. Although traditionally used for revealing lateral electrical conductivity (EC) patterns, e.g., to produce maps of salinity or water content, FDEM inversion is increasingly used to produce depth-specific models of EC. These quantitative models can be used to inform several depth-specific properties relevant to hydrological modeling (e.g. depths to interfaces and soil water content). Material and methods: There are a number of commercial FDEM instruments available; this work compares a multi-coil device (i.e., a single-frequency device with multiple receiver coils) and a multi-frequency device (i.e., a single receiver device with multiple frequencies) using the open-source software EMagPy. Firstly, the performance of both devices is assessed using synthetic modeling. Secondly, the analysis is applied to field data from an alpine catchment. Results: Both instruments retrieved a similar EC model in the synthetic and field cases. However, the multi-frequency instrument displayed shallower sensitivity patterns when operated above electrically conductive grounds (i.e., 150 mS/m) and therefore had a lower depth of investigation. From synthetic modeling, it also appears that the model convergence for the multi-frequency instrument is more sensitive to noise than the multi-coil instrument. Conclusion: Despite these limitations, the multi-frequency instrument is smaller and more portable; consequently, it is easier to deploy in mountainous catchments.